Teachers´ attitude (Journal of Parents and Teachers, 2013)
If teachers were emotionally competent, the classrooms would be safe places with exquisite coexistence and continuous learning acquisition. Considering the three edges of the teacher and students’ effectiveness: to want, to know and to be able, the key in on the attitude with which the everyday challenges that the class presents are faced. So it is essential to reflect about the self-attitude, principally stressing the detection of our potentials and dysfunctions or the competences we have to train in order to improve the classroom management ability.
Keywords: attitude; teacher training; classroom management; skills; emotions